Investigating the effects of goal conflict and trait self-control on the intention-behaviour relationship in emerging adulthood - Haider, Imran (My University, 2022)
Background: The transition into emerging adulthood is a major developmental period in one’s life in which rapid declines in physical activity (PA) are documented. While many emerging adults possess intentions to engage in regular PA, evidence suggests acting on these intentions represents a significant challenge. Obtaining a deeper understanding of the factors associated with the process of translating emerging adult’s PA intentions into action may be integral in building a healthier adult population. The purpose of the study was to investigate the effects of two potential moderators of the PA intention-behaviour relationship: goal conflict and trait self-control, in a sample of emerging adults. Methods: The study sample was comprised of 132 participants (Mage = 17.80 ± 0.46; 64% female) drawn from a larger prospective cohort study (ADAPT Study). All participants completed two online questionnaires, approximately four weeks apart. Measures of PA intention strength, goal conflict and trait self-control were assessed at time 1. At time 2, participants completed a measure of self-reported moderate-to-vigorous physical activity (MVPA) engagement. Four moderation analyses were performed to assess the independent and combined effects of goal conflict and trait self-control on the PA intention-behaviour relationship. Results: Across all moderation analyses, the main effect of intention strength was significant (p < 0.001), providing support for the necessary role it plays in PA behaviour. However, the main effects of goal-conflict and trait self-control were not found to be significant, along with all interaction effects tested. Correlational analyses revealed intention strength (r = 0.346, p < .001) and goal-conflict (r = -0.236, p < 0.05) were significantly correlated with MVPA, however trait self-control (r = 0.048) was not. Conclusion: Although results showed a modest intention-PA relationship, the hypothesized moderating effects of goal conflict and self-control were not supported. While the subjective perception of one’s self-control ability did not moderate the intention-behaviour relationship, future research should explore the interaction between goal conflict and self-control further using more objective measures, or in combination with self-regulation strategies such as action and coping planning. Additionally, goal prioritization may be an important factor to consider when investigating the effect of goal conflict on PA and the intention-PA relationship.
Keywords: Intention-Behaviour Gap; Physical Activity; Emerging Adulthood; Moderation